Pilot-scale membrane distillation modeling: Validation, comparison, and consensus - Martijn Bindels; Juan A. Andrés-Mañas; Weijian Ding; Ivaylo Hitsov; Oyku Mutlu-Salmanli; Mukta Hardikar; Tzahi Y. Cath; Johan Vanneste; Radisav D. Vidic; Andrea Achilli; Ritesh Pawar; Ismail Koyuncu; et al. (Desalination, 2026)

Rapid wall shear stress prediction for aortic aneurysms using deep learning: a fast alternative to CFD - Md. Ahasan Atick Faisal; Onur Mutlu; Sakib Mahmud; Anas Tahir; Muhammad E. H. Chowdhury; Faycal Bensaali; Abdulrahman Alnabti; Mehmet Metin Yavuz; Ayman El-Menyar; Hassan Al-Thani; Huseyin Cagatay Yalcin (Medical & Biological Engineering & Computing, 2025)
Aortic aneurysms pose a significant risk of rupture. Previous research has shown that areas exposed to low wall shear stress (WSS) are more prone to rupture. Therefore, precise WSS determination on the aneurysm is crucial for rupture risk assessment. Computational fluid dynamics (CFD) is a powerful approach for WSS calculations, but they are computationally intensive, hindering time-sensitive clinical decision-making. In this study, we propose a deep learning (DL) surrogate, MultiViewUNet, to rapidly predict time-averaged WSS (TAWSS) distributions on abdominal aortic aneurysms (AAA). Our novel approach employs a domain transformation technique to translate complex aortic geometries into representations compatible with state-of-the-art neural networks. MultiViewUNet was trained on $$\varvec{23}$$ 23 real and $$\varvec{230}$$ 230 synthetic AAA geometries, demonstrating an average normalized mean absolute error (NMAE) of just $$\varvec{0.362%}$$ 0.362 % in WSS prediction. This framework has the potential to streamline hemodynamic analysis in AAA and other clinical scenarios where fast and accurate stress quantification is essential. Graphical abstract

Trastuzumab deruxtecan (DS-8201a), a HER2-targeting antibody–drug conjugate, demonstrates in vitro and in vivo antitumor activity against primary and metastatic ovarian tumors overexpressing HER2 - Levent Mutlu; Blair McNamara; Stefania Bellone; Diego D. Manavella; Cem Demirkiran; Michelle Greenman; Miguel Skyler Z. Verzosa; Natalia Buza; Pei Hui; Tobias Max Philipp Hartwich; Justin Harold; Yang Yang-Hartwich; et al. (Clinical & Experimental Metastasis, 2024)

Phylogeny and systematics of the Lactucinae (Asteraceae) focusing on their SW Asian centre of diversity - Murat E. Güzel; Kamil Coşkunçelebi; Norbert Kilian; Serdar Makbul; Mutlu Gültepe (Plant Systematics and Evolution, 2021)

Correction to: On the use of hierarchical fuzzy inference systems (HFIS) in expert-based landslide susceptibility mapping: the central part of the Rif Mountains (Morocco) - B. C. Ozer; B. Mutlu; H. A. Nefeslioglu; E. A. Sezer; M. Rouai; A. Dekayir; C. Gokceoglu (Bulletin of Engineering Geology and the Environment, 2020)

On the use of hierarchical fuzzy inference systems (HFIS) in expert-based landslide susceptibility mapping: the central part of the Rif Mountains (Morocco) - B. C. Ozer; B. Mutlu; H. A. Nefeslioglu; E. A. Sezer; M. Rouai; A. Dekayir; C. Gokceoglu (Bulletin of Engineering Geology and the Environment, 2020)

PBDE-47 and PBDE mixture (DE-71) toxicities and liver transcriptomic changes at PND 22 after in utero/postnatal exposure in the rat - J. K. Dunnick; K. R. Shockley; A. R. Pandiri; G. E. Kissling; K. E. Gerrish; T. V. Ton; R. E. Wilson; S. S. Brar; A. E. Brix; S. Waidyanatha; E. Mutlu; D. L. Morgan (Archives of Toxicology, 2018)

First occurrence of knight rock shrimp, Sicyonia lancifer (Olivier, 1811) (Decapoda: Sicyoniidae) in the Mediterranean Sea. - A. PATANIA; E. MUTLU (Mediterranean Marine Science, 2015)
The occurrence of the non-native species Sicyonia lancifer (Olivier, 1811) belonging to Sicyoniidae family is reported for the first time in the Mediterranean Sea. In the following paper the distinguishing features of the species are provided.

The features of infectious diseases departments and anti-infective practices in France and Turkey: a cross-sectional study - H. Erdem; J. P. Stahl; A. Inan; S. Kilic; M. Akova; C. Rioux; I. Pierre; A. Canestri; E. Haustraete; D. O. Engin; E. Parlak; X. Argemi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

On the Occurrence and Established Populations of the Alien Polychaete Polydora cornuta Bosc, 1802 (Polychaeta: Spionidae) in the Sea of Marmara and the Bosphorus Strait (Turkey) - S.U. KARHAN; E. KALKAN; N. SIMBOURA; E. MUTLU; M. BEKOLET (Mediterranean Marine Science, 2008)
The present paper reports the first occurrence of Polydora cornuta in the Bosphorus Strait and its finding in a new locality in the Sea of Marmara, providing a link with its Aegean and Black Sea populations. The probable vector for the introduction of P. cornuta into the Sea of Marmara is shipping through the Dardanelles Strait. Both soft and hard-bottom populations were examined and the importance and prevalence of this species within the native macrozoobenthic communities were elucidated. Its abundance ranged between 40 and 3390 ind.m-2 (mean:1320 ±1199.45 SD) and its percent contribution to the total faunal populations ranged between 3.31 and 75.56 (mean:27.79 ±25.00 SD) in the Sea of Marmara softbottom community. During the sampling period, P. cornuta contributed little to the total faunal abundance of the hard-bottom communities in the Bosphorus Strait. Its mean abundance in the hard substrate ranged between 8.33 and 1000 ind.m-2 (mean:117.36 ±279.73 SD) and its percent contribution to the total faunal populations ranged between 0.02 and 21.86 (mean:2.07 ±6.25 SD).The role of this invasive species in the soft-bottom macrobenthic community at an organically enriched site examined in the Sea of Marmara is highlighted, and a comparison with Aegean Sea populations of the species is also included.

Application of the bentix index in assessing ecological quality of hard substrata: a case study from the Bosphorus Strait, Turkey - E. KALKAN; S.U. KARHAN; E. MUTLU; N. SIMBOURA; M. BEKOLET (Mediterranean Marine Science, 2007)
In this paper, a biotic index (Bentix) has been used for the assessment of ecological quality status of shallow water hard substrate benthic ecosystems affected by coastal sewage discharges in the Bosphorus Strait. A significant difference was observed between the control and the discharge stations with regard to Bentix values (Mann-Whitney U Test, p=0.002) and ecological quality status of the discharge stations was worse than that of controls. The index values revealed that sewage discharges caused serious disturbance in macrozoobenthic communities in the area investigated. Although so far it has been used for soft bottom communities, Bentix (with some species scoring modifications) also appeared to work successfully in hard substrates, at least for the present study.

Changes in Summer Irrigated Crop Area and Water Use in Southeastern Turkey from 1993 to 2002: Implications for Current and Future Water Resources - Mutlu Ozdogan; Curtis E. Woodcock; Guido D. Salvucci; Hüseyin Demir (Water Resources Management, 2006)

Sexual dimorphisms in radula of Conomurex persicus (Gastropoda: Strombidae) in the Mediterranean Sea - E. Mutlu (Marine Biology, 2003)

Distribution and abundance of moon jellyfish ( Aurelia aurita ) and its zooplankton food in the Black Sea - E. Mutlu (Marine Biology, 2001)

Distribution and abundance of ctenophores and their zooplankton food in the Black Sea. II. Mnemiopsis leidyi - E. Mutlu (Marine Biology, 1999)

Distribution and abundance of ctenophores, and their zooplankton food in the Black Sea. I. Pleurobrachia pileus - E. Mutlu; F. Bingel (Marine Biology, 1999)